Kharkov data on pion photoproduction and Δ⁺(1232) resonance parameters - Omelaenko, A.S. (Вопросы атомной науки и техники, 2003)
We present the analytic review of π⁺ and π⁰ mesons photoproduction off the proton target as the only source of information about the Δ⁺(1232) resonance parameters. The review focuses at the estimation of the influence of different contributions to the experimental database on determination of the E2/M1 ratio for γp→Δ⁺ transition and the resonance parameters, with discussion of the previous Kharkov results. Представлено аналітичний огляд фотонародження π⁺ та π⁰ мезонів на протонній мішені як єдиного джерела інформації про параметри Δ⁺(1232)-разонанса. Огляд фокусується на оцінці впливу різних вкладів в экспериментальну базу даних на визначення E2/M1-відношення для γp→Δ⁺ переходу і параметрів резонанса, з обговоренням отриманих раніше в Харкові результатів. Представлен аналитический обзор фоторождения π⁺ и π⁰ мезонов на протонной мишени как единственный источник информации о параметрах Δ⁺(1232)-разонанса. Обзор фокусируется на оценке влияния различных вкладов в экспериментальную базу данных на определение E2/M1-отношения для γp→Δ⁺ перехода и параметров резонанса, с обсуждением полученных ранее в Харькове результатов.